2015
DOI: 10.1038/nmat4214
|View full text |Cite
|
Sign up to set email alerts
|

Predicting nonlinear properties of metamaterials from the linear response

Abstract: The discovery of optical second harmonic generation in 1961 started modern nonlinear optics. Soon after, R. C. Miller found empirically that the nonlinear susceptibility could be predicted from the linear susceptibilities. This important relation, known as Miller's Rule, allows a rapid determination of nonlinear susceptibilities from linear properties. In recent years, metamaterials, artificial materials that exhibit intriguing linear optical properties not found in natural materials, have shown novel nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
262
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(271 citation statements)
references
References 30 publications
7
262
0
Order By: Relevance
“…This seems to be also responsible for the recently observed broadband THz generation under femtosecond near-infrared laser excitation in an array of gold SRRs [237]. It was also shown that the geometry of resonators, particularly the asymmetry ratio, plays a critical role because of the mode overlap [238]. Although the nonlinear coefficients were enhanced by orders of magnitude, the absolute conversion efficiency is still rather low.…”
Section: Nonlinear Metasurfacesmentioning
confidence: 93%
“…This seems to be also responsible for the recently observed broadband THz generation under femtosecond near-infrared laser excitation in an array of gold SRRs [237]. It was also shown that the geometry of resonators, particularly the asymmetry ratio, plays a critical role because of the mode overlap [238]. Although the nonlinear coefficients were enhanced by orders of magnitude, the absolute conversion efficiency is still rather low.…”
Section: Nonlinear Metasurfacesmentioning
confidence: 93%
“…Moreover, the third order nonlinear optical response of the proposed chiral metamaterials under illumination of a circularly polarized FW is numerically calculated using FEM method based on nonlinear scattering theory. 32 In the calculations, we first simulate the linear optical fields (E ω ) at the fundamental wavelength, which are assumed to be unaffected by the up-conversion process. The nonlinear polarization induced in the bulk of the nanostructure is then calculated by P 3ω = ε 0 χ (3) .…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…In metamaterials and nanostructures the application of Miller's rule is not straightforward. For example, it holds for third harmonic generation (THG), but fails for SHG, which can be explained by the nonlinear scattering model [28]. Examples of nonlinear near-field control in nanostructures have recently been reported [23,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it holds for third harmonic generation (THG), but fails for SHG, which can be explained by the nonlinear scattering model [28]. Examples of nonlinear near-field control in nanostructures have recently been reported [23,[28][29][30][31]. The nonlinear emission control is even more challenging in hybrid dielectric/plasmonic nanostructures, since the nonlinear optical generation can take place in the gap of the nanoantenna due to the presence of a nonlinear material, in the nonlinear dielectric surrounding the nanostructure, or in the nanostructure material itself [32].…”
Section: Introductionmentioning
confidence: 99%